2013
DOI: 10.4236/ojas.2013.34a1001
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of <i>Culex quinquefasciatus</i> (Diptera: Culicidae) to malathion in Sargodha district, Pakistan

Abstract: The present study was designed to evaluate the susceptibility of Culex quinquefasciatuns against malathion in Sargodha district of Pakistan. The activities of detoxifying enzymes i.e., β-esterases, GSTs and monooxygenases were also estimated. Our results revealed 100 percent mortality in insecticide treated groups after 24 hours of exposure. There was no difference in the activities of insecticide detoxifying enzymes between control and treated groups. We concluded from our work that malathion is still effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Gambiae and Cx. quinquefasciatus in this study, is similar to the research findings of Corbel et al, 2007 , Tahir et al, 2013 , Opara et al, 2017 , Boussougou-Sambe et al, 2018 , Fagbohun et al, 2020 , in West Africa, Nigeria, South-east Asian, and Malaysia, their reports revealed the susceptible status of these mosquitoes to malathion with KDT 50 lower mortality time range values 21.50–23.30 mins while comparing to this current study. Nevertheless, this result is contrary to the report by ( Norris & Norris, 2011 ), which showed resistance to malathion in Macha, Zambia after 24hr exposure period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gambiae and Cx. quinquefasciatus in this study, is similar to the research findings of Corbel et al, 2007 , Tahir et al, 2013 , Opara et al, 2017 , Boussougou-Sambe et al, 2018 , Fagbohun et al, 2020 , in West Africa, Nigeria, South-east Asian, and Malaysia, their reports revealed the susceptible status of these mosquitoes to malathion with KDT 50 lower mortality time range values 21.50–23.30 mins while comparing to this current study. Nevertheless, this result is contrary to the report by ( Norris & Norris, 2011 ), which showed resistance to malathion in Macha, Zambia after 24hr exposure period.…”
Section: Discussionsupporting
confidence: 92%
“…quinquefasciatus has proved resistant to malathion and carbamate insecticides in the Eastern, Central, and Western parts of Cuba. Also Tahir et al, 2013 reported the susceptibility of Cx. quinquefasciatus on malathion in Pkistan.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes are vector agents that cause diseases by transmitting the virus and parasite from one person to another [1] . Mosquitoes are the major public health pests and are vectors for many diseases, such as malaria and West Nile Virus [2] .…”
Section: Introductionmentioning
confidence: 99%